2015
DOI: 10.1038/srep16164
|View full text |Cite
|
Sign up to set email alerts
|

Strain assisted electrocaloric effect in PbZr0.95Ti0.05O3 films on 0.7Pb(Mg1/3Nb2/3)O3-0.3PbTiO3 substrate

Abstract: Solid state cooling technologies based on electrocaloric, magnetocaloric and mechanocaloric effects have received much attention during the past decade. To further improve the cooling efficiency and reduce the driving field, it is desirable to combine multiple effects in a single system. Here, we report on the caloric effects induced by both electric field and strain in PbZr0.95Ti0.05O3 films deposited on 0.7Pb(Mg1/3Nb2/3)O3-0.3PbTiO3 substrate. The isothermal entropy change (ΔS) induced by the antiferroelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…The Ragone profile showed that this HSC achieved a maximum volumetric (gravimetric) energy density value of 10.1 mWh cm −3 (139.9 Wh kg −1 ) at a volumetric power value of 167.4 mW cm −3 (2310 W kg −1 ) (139.8 μWh cm −2 at 2310 μW cm −2 ) (Figure 4h; Figure S26c,d, Supporting Information). This energy density value was higher than those of several previous research works, including Ag: BiVO 4 /Ag: BiVO 4 (2.63mWh cm −3 ), [33] CNTs//Li 4 Ti 5 O 12 (4.38 mWh cm −3 ), [34] NiSe//AC (0.26 mWh cm −3 ), [35] MnO 2 @CF//FeOOH/PPy@CF (2 mWh cm −3 ), [36] NiCo LDH/3D-Ni//Mn 3 O 4 /3D-Ni (4.59 mWh cm −3 ), [37] etc.…”
Section: Resultscontrasting
confidence: 57%
“…The Ragone profile showed that this HSC achieved a maximum volumetric (gravimetric) energy density value of 10.1 mWh cm −3 (139.9 Wh kg −1 ) at a volumetric power value of 167.4 mW cm −3 (2310 W kg −1 ) (139.8 μWh cm −2 at 2310 μW cm −2 ) (Figure 4h; Figure S26c,d, Supporting Information). This energy density value was higher than those of several previous research works, including Ag: BiVO 4 /Ag: BiVO 4 (2.63mWh cm −3 ), [33] CNTs//Li 4 Ti 5 O 12 (4.38 mWh cm −3 ), [34] NiSe//AC (0.26 mWh cm −3 ), [35] MnO 2 @CF//FeOOH/PPy@CF (2 mWh cm −3 ), [36] NiCo LDH/3D-Ni//Mn 3 O 4 /3D-Ni (4.59 mWh cm −3 ), [37] etc.…”
Section: Resultscontrasting
confidence: 57%
“…The acquired quadratic increase of EC entropy and temperature change with E successfully reproduces the ∆ T changes with E 2 in dipole glasses 28 measured as early as in 1965 and the recently-proposed quadratic scaling law of ∆ T in PbZrO 3 AFE 29 . It is also worth noting that both the proportional increase and the saturating trend of either ∆ T or (−∆ S ) are frequently observed in pretty rich low-dimensional EC materials 30 34 .…”
Section: Resultsmentioning
confidence: 94%
“…( c ) Direct comparison of calculated (−∆S) curves vs E with two sets of indirect experimental data in PZT AFE thin film. The BaTiO 3 , P(VDF-TrFE-CFE), 0.65PMN-0.35PT, BZT, PLZT and PZT data is derived from refs 11 , 30 , 31 , 32 , 33 and 34 , respectively. …”
Section: Resultsmentioning
confidence: 99%
“…There are few reports on wearable LIBs/LICs, and research on this topic is in progress. Zuo et al [66] reported a flexible LIC with excellent energy and power characteristics using LTO/carbon cloth for the first time. These researchers constructed a thin-film HSC with binder-free electrodes where the active material is directly grown on a highly porous and conductive carbon cloth (Figure 5a).…”
Section: Flexible Licsmentioning
confidence: 99%